Pengolahan Sampah Ramah Lingkungan Dengan Metode Ecobrick Dan Compostbag Di Kelurahan Kedungdoro - Mirah Sandika; Agung Pujianto; Febby Rahmatullah Masruchin; Anang Suharyanto (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Community service is an activity that aims to help certain communities in several activities, students as companions for residents of RW 11 Kedungdoro sub-district regarding the Free Learning Campus Free Program (MBKM) Kampung Zero Waste (KZW) in collaboration with the Surabaya City Environmental Service, in socializing internal waste processing. Environmentally friendly media ecobricks and compost bags which aim to reduce waste generation, this activity uses the observation method, students observe the environment of rw 11 kedungdoro sub-district by going directly into the field.